The Relationship of Macro And Micro Nutrients With The Incidence of Anemia in Adolescent Girls at Smp Plus Al Muhsinin Cangkuang District, Bandung Regency - Desy Anggraeni; Yuliati Widiastuti; Iriyanti Harun (Saintify Publish, 2024)
Adolescent girls are a population at risk of iron deficiency due to increased nutrient requirements during growth. The high incidence of anemia among adolescents will continue into adulthood if not handled properly. Problems that will be experienced are pallor, fatigue, dizziness and the ability to concentrate on learning. The purpose of the study was to determine the relationship between macronutrients and micronutrients with the incidence of anemia in adolescent girls at SMP Plus Al Muhsinin in Cangkuang District. This research method uses a cross sectional design of 35 respondents who come from Al Muhsinin Plus Junior High School students in Cangkuang District. This research method used a cross-sectional design on 35 respondents from students of SMP Plus Al Muhsinin in Cangkuang District. Data were collected on nutrient intake using the Semi Quantitative Food Frequency Questionnaire (SFFQ) and the value of hemoglobin levels using the hemoglobin blood test (GCHb). The results of statistical tests using chi-square showed there was a significant relationship between carbohydrate intake with a value of (p = 0.009), protein intake with a value of (p = 0.001), fat intake with a value of (p = 0.004), iron intake with a value of (p = 0.004), vitamin C intake with a value of (p = 0.016), folic acid intake with a value of (p = 0.016). There was no significant relationship in zinc intake with a value of (p = 1,000). It is expected that schools can make healthy canteens and healthy breakfast movements routinely 2x a week and form teams and youth cadres as supervisors of fe tablet consumption.